Frequency of urinary tract infection in children with antenatal diagnosis of urinary tract dilatation. Issue 3 (28th August 2019) - Pennesi, Marco; Amoroso, Stefano; Bassanese, Giulia; Pintaldi, Stefano; Giacomini, Giulia; Barbi, Egidio
Abstract : Background: Neonates with congenital urinary tract dilatation (UTD) may have an increased risk of urinary tract infections (UTI). At present, the management of these patients is controversial and the utility of continuous antibiotic prophylaxis (CAP) remains uncertain as the literature presents contradicting evidence. The aim of this observational study was to assess UTI occurrence in children with prenatal diagnosis of urinary collecting system dilatation without antibiotic prophylaxis. Methods: Between June 2012 and August 2016, we evaluated the incidence of UTI and the clinical and ultrasonography evolution in 407 children with a prenatally diagnosed UTD. All subjects underwent two prenatal ultrasounds scans (USs) at 20 weeks and 30 weeks of gestation and within 1 month of birth. Patients with a confirmed diagnosis of UTD underwent US follow-up at 6, 12 and 24 months of life. According to the UTD classification system stratify risk, after birth UTD were classified into three groups: UTD-P1 (low risk group), UTD-P2 (intermediate risk group), and UTD-P3 (high risk group). Voiding cystourethrogram was performed in all patients who presented a UTI and in those with UTD-P3. No patient underwent CAP. Results: Postnatal US confirmed UTD in 278 out of 428 patients with the following rates: UTD-P1 (126), UTD-P2 (95) and UTD-P3 (57). During postnatal follow-up, 6.83% patients presented a UTI (19 out of 278). Eleven out of 19 had vesicoureteral reflux (VUR), and other four were diagnosed with obstructive uropathy and underwent surgical correction. Five patients presented a UTI reinfection. Conclusion: The occurrence of UTI in patients with urinary collecting system dilatation was low. The recent literature reports an increased selection of multirestistant germs in patients with VUR exposed to CAP. This study constitutes a strong hint that routine continuous antibiotic prophylaxis could be avoided in patients with UTD.